A conserved pathway of transdifferentiation in murine Kupffer cells. Issue 10 (13th August 2021) - Li, Xinyu; Hollingshead, Nicole; Lampert, Sarah; Truong, Camtu D.; Li, Wanyu; Niu, Junqi; Crispe, Ian N.; Soysa, Radika
Abstract: Abundant long‐lived liver‐resident macrophages, termed Kupffer cells, are activated during chronic liver injury. They secrete both pro‐inflammatory and pro‐fibrotic cytokines, which act on hepatic stellate cells causing their transdifferentiation into myofibroblasts that deposit collagen. In other tissues, wound‐associated macrophages go further, and transdifferentiate into fibrocytes, secreting collagen themselves. We tested Kupffer cells for this property in two experimental models: mixed non‐parenchymal cell culture, and precision‐cut liver slice culture. Using the Emr1‐Cre transgene as a driver and the RiboTag transgene as a reporter, we found that Kupffer cells undergo transdifferentiation under these circumstances. Over time, they lose the expression of both Kupffer cell‐specific and macrophage‐specific genes and the transcription factors that control their expression, and they begin to express multiple genes and proteins characteristic of either myofibroblasts or tissue fibroblasts. These effects were strongly conserved between non‐parenchymal cell culture and liver tissue slice culture, arguing that such transdifferentiation is a conserved function of Kupffer cells. We conclude that in addition to supporting fibrosis through an action on stellate cells, Kupffer cells also participate in liver fibrosis through transdifferentiation into fibrocytes. Abstract : Kupffer cells are the long‐lived macrophages of the liver. Using a Emr1‐Cre::RiboTag‐based lineage tracing model combined with a slice culture system we show that these Kupffer cells survive and respond to culture conditions by changing their gene expression. Gene expression analysis indicated that in the culture Kupffer‐derived cells transdifferentiated into a fibrocyte‐like cell type while renouncing their macrophage identity.